Contexts of nursing an introduction - Daly, John 1958-; Speedy, Sandra; Jackson, Debra 1959- (Elsevier Australia (a division of Reed International Books Australia Pty Ltd., 2017)
Contexts of Nursing: An Introduction, 5th edition provides comprehensive coverage of the key ideas underpinning contemporary nursing practice in Australia and New Zealand. Each chapter introduces nursing students to the big issues in nursing and healthcare, highlighting the theory, language, research and debate in a way that will challenge the reader and encourage reflection and discussion.